Development of bitumen from industrial wastes - Razali, Mohd Najib (2018)
Bitumen is produced from crude oil extracted from the ground, which categorizes crude oil as one of the non-renewable fossil fuels. Various environmental issues that have risen in Malaysia are caused by the excessive manufacturing activities and the miss-management of industrial wastes. In an effort to mitigate these issues, industrial wastes are being used in various EMB formulations. Industrial wastes, such as polystyrene, polyethylene, and used automotive oil can be used as alternatives to formulate bitumen. Normally, a suitable emulsifier is needed to produce the final product, which is EMB. The emulsifier will yield a charge, depending on its properties, to bind the oily bitumen with water. In this current study, physical characteristic studies were performed using thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), flash point test, density test, and moisture content test. Fourier Transform Infrared Spectroscopy (FTIR) analysis was also performed to determine the material‟s molecular composition and structure. These tests was performed in order to choose the best material for the experiment The method that was used to formulate this product was heating and mixing that was done inside the fume hood. So that it can absorb the fume released while the experiment was conducted. The key parameters for this process are weight of the sample, temperature, time, speed of the mixer and the emulsifier used. Firstly, the raw materials were characterized by using analytical method such as TGA, DSC, Density test and Flash point test. Once the polymer modified bitumen was produced, the sample was analyse based on penetration @ 25oC test using ASTM D5 method and softening point test, ASTM D36 method. The polymer modified bitumen formulated was then being emulsified to become EMB and was compared with industrial grade bitumen emulsion (80/100) from Kemaman Bitumen Company. From the result, the best ratio of bitumen emulsion is (2:0.5.7.5) for formulation without crumb rubber and (20:2:39:39) formulation with crumb rubber since both substance was perfectly soluble in the mixture and it is having 200/300 penetration value, 34℃ of softening point. Thus it is the most suitable one for waterproofing wall application.